2016
DOI: 10.1002/hed.24272
|View full text |Cite
|
Sign up to set email alerts
|

Temporal course and predictive factors of analgesic opioid requirement for chemoradiation‐induced oral mucositis in oropharyngeal cancer

Abstract: Opioid therapy remains the mainstay for OM-related pain management during CRT. The role of previous smoking and HPV on opioid use needs further confirmations. © 2016 Wiley Periodicals, Inc. Head Neck 38: E1521-E1527, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 26 publications
1
27
0
Order By: Relevance
“…It is interesting to note the double pattern of toxicities in HPV-related diseases: in the acute phase, incidence of mucositis, dysphagia, and opioids use are higher in HPV-positive cancers than in their negative counterpart [33,34]; in the late period, however, the rate of toxicities changes in these 2 groups as showed by our results. HPV-positive microenvironment (richer in effector T cells, cytokines and chemokines) may explain the higher level of acute inflammation [35].…”
Section: Discussionsupporting
confidence: 53%
“…It is interesting to note the double pattern of toxicities in HPV-related diseases: in the acute phase, incidence of mucositis, dysphagia, and opioids use are higher in HPV-positive cancers than in their negative counterpart [33,34]; in the late period, however, the rate of toxicities changes in these 2 groups as showed by our results. HPV-positive microenvironment (richer in effector T cells, cytokines and chemokines) may explain the higher level of acute inflammation [35].…”
Section: Discussionsupporting
confidence: 53%
“…A retrospective study showed that opioid therapy remains a corner stone for OM pain management in CCRT, as suggested by the MASCC/ISOO guidelines (33, 198). …”
Section: Symptomatic Treatment Of Riommentioning
confidence: 99%
“…Eighty to 100% of adult patients who undergo radiotherapy with or without concurrent chemotherapy for head and neck cancer will experience oral mucositis as a painful side effect of their cancer treatment. 1 , 4 , 9 , 16 Oral mucositis is painful damage to the mucosa in the oral cavity and the pharynx and is associated with vital oral dysfunction such as swallowing problems. 3 It has been identified by patients as the most severe side effect associated with cancer treatment in head and neck cancer patients as it induces severe problems with eating, drinking, and speaking.…”
Section: Introductionmentioning
confidence: 99%
“… 3 It has been identified by patients as the most severe side effect associated with cancer treatment in head and neck cancer patients as it induces severe problems with eating, drinking, and speaking. 1 , 3 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation